Prostaglandin E2 Inhibits Prostate Cancer Progression by Countervailing Tumor Microenvironment-Induced Impairment of Dendritic Cell Migration through LXRα/CCR7 Pathway - Kuang Youlin; He Weiyang; Liang Simin; Gou Xin (Journal of Immunology Research)
Migration and homing of dendritic cells (DCs) to lymphoid organs are quite crucial for T cell-induced immune response against tumor. However, tumor microenvironment can make some tumor cells escape immune response by impairing DC migration. Prostaglandin E2 (PGE2) plays important roles in initiating and terminating inflammatory responses. In this study, we investigated whether PGE2 could inhibit murine prostate cancer progression by countervailing tumor microenvironment-induced impairment of dendritic cell migration. We found that murine prostate cancer cell line RM-1-conditioned medium impaired chemotactic movement of marrow-derived DCs and splenic cDCs toward CC chemokine receptor-7 (CCR7) ligand CCL19 in vitro and migration to draining lymph gland in vivo. Meanwhile, it also induced LXRα activation and CCR7 inhibition on maturing DCs. However, the treatment of PGE2 rescued this impairment of DC migration with upregulation of CCR7 and inhibition of LXRα. Further, it was observed that PGE2 also increased MMP9 expression and activated Notch1 signaling on DCs. In RM-1-bearing mouse model, PGE2 treatment was identified to inhibit tumor growth and induce more tumor-infiltrating T cells and CD11c dendritic cells in tumor sites. Therefore, our findings may demonstrate a new perspective for therapeutic interventions on prostate cancer immunoescape.